Comparison of Cognitive Function and Depressive Symptoms in Older Adults Engaged and Not Engaged in Exercise: Analysis Using the AMT and GDS - Wahid, Wahyana Mujari (Indonesian Journal of Physical Education and Sport Science, 2025)
Studi purpose. This study aims to analyze differences in the level of mental function and depression in the elderly who are active and inactive in gymnastics, using the Abbreviated Mental Test (AMT) and Geriatric Depression Scale (GDS) instruments. Materials and methods. The research design used was comparative with a sample size of 40 elderly, consisting of 20 elderly active gymnastics and 20 elderly not active gymnastics. Data collection was carried out through AMT and GDS questionnaires, while data analysis used independent samples t-test. Results. The results showed the average AMT score in the elderly who were not active in gymnastics was 8.85 (SD = 2.23) and in the elderly who were active in gymnastics was 9.70 (SD = 0.73), with a p value = 0.114. Both groups were in the normal category for cognitive function. In the GDS score, the elderly inactive gymnastics had an average of 9.15 (SD = 6.94) and the elderly active gymnastics of 10.00 (SD = 5.52), with a p value = 0.670. By interpretation, the inactive group was in the normal category, while the active group was at the initial limit of the mild depression category. Nonetheless, the two groups showed no significant difference in terms of mental function or level of depression. Conclusions. This finding indicates that gymnastic activities performed once a week are not enough to have a significant impact on mental function and depression in the elderly. Therefore, it is necessary to consider encouraging the implementation of more intense and structured physical activities to meet the physical and mental health needs of the elderly optimally. Keywords: elderly, AMT, GDS, physical activity.